2017
DOI: 10.1055/s-0037-1604084
|View full text |Cite
|
Sign up to set email alerts
|

Early Dynamics of Interleukin-6 in Cerebrospinal Fluid after Aneurysmal Subarachnoid Hemorrhage

Abstract: Early dynamics of IL-6 in CSF are associated with a patient́s outcome. But it is difficult to use IL-6 alone for outcome prediction due to its high variability. The question is whether the dynamics of IL-6 could be used in combination with other early markers associated with brain injury. More detailed research is required to answer this question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…However, neuroinflammation after SAH plays an important role in the pathophysiologic events of EBI, as mentioned above, and proinflammatory cytokines, such as IL-1β, IL-6, and TNF-α, are mediators of those immunologic reactions and are associated with the neurologic outcome [24,25]. Therefore, we intend to further study the effect of SGB on the changes of inflammatory cytokine levels and cerebral blood vessels during EBI and to discuss the effect of SGB on the clinical prognosis of patients with SAH.…”
Section: Introductionmentioning
confidence: 99%
“…However, neuroinflammation after SAH plays an important role in the pathophysiologic events of EBI, as mentioned above, and proinflammatory cytokines, such as IL-1β, IL-6, and TNF-α, are mediators of those immunologic reactions and are associated with the neurologic outcome [24,25]. Therefore, we intend to further study the effect of SGB on the changes of inflammatory cytokine levels and cerebral blood vessels during EBI and to discuss the effect of SGB on the clinical prognosis of patients with SAH.…”
Section: Introductionmentioning
confidence: 99%
“… 37 Other studies showed that the expression levels of IL-6 in CSF were associated with outcomes in aSAH patients. 21 , 25 , 33 Elevated IL-6 levels in CSF may induce neuroinflammation and may be closely linked to the progression of delayed cerebral ischemia after SAH. 24 IL-6 and TNF-α in CSF could be essential biomarkers for disease prediction and disease monitoring in SAH patients.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 23 , 24 Studies reported that elevated IL-6 levels induce neuroinflammation and may be closely associated with the outcomes of aSAH. 20 , 25 , 26 Nevertheless, screens for the expression IL-6 of sEVs in CSF of aSAH patients have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For ST, they have anti-vasospasm and anti-in ammatory effects. Vasospasm is closely related to the DCI process after aSAH, but the in ammatory mechanism runs throughout the EBI and DCI brain injury process [48][49][50][51] . Several different trials [52][53][54][55] indicated that the e cacy of statins is still controversial, although ST failed to show a good ability to improve clinical outcome in our study, given the important role of nerve in ammation in the process of aSAH and the relative safety of ST, we believe that ST still has great potential, and may be used in combination with other drugs to produce curative effect in terms of improving the prognosis of patients with signi cant synergistic effect.…”
Section: Discussionmentioning
confidence: 99%